Occupational Health Risk Management in Tablet Manufacturing: A Case Study of Non-Beta Lactam and Penicillin Production Units - Arie Arizandi Kurnianto; Reski Syamsu; Peter Thokozani Phiri; Josfirin Uding Rangga (Tecno Scientifica Publishing, 2025)
Background: In the pharmaceutical tablet manufacturing industry, health risks involve high occupational health risks, especially in handling active pharmaceutical ingredients (APIs). This research addresses the challenge that effective risk management is essential to safeguard worker health, particularly in the production of critical products such as Non-Beta Lactams (NBL) and Penicillin. Objective: evaluating and investigating occupational health risks in the NBL and Penicillin production units, identifying key risk factors and proposing strategies to reduce exposure. Methods: This study used an observational cross-sectional design was used, focusing on environmental conditions, particulate concentrations, and compliance with personal protective equipment (PPE). The framework based on the concept of Hazard Identification and Risk Assessment (HIRA) assessed the level of risk across all stages of production, including weighing, mixing, granulation, and coating. Findings: Unit NBL indicated higher particulate levels (140 µg/m³) compared to unit Penicillin (100 µg/m³), especially during high exposure stages such as granulation, exceeding the WHO guideline (PM2.5 exposure is 25 µg/m³ for a 24-hour period) . The compliance with PPE was found to be lower in the NBL unit, which correlated with an increased incident rate. The risk assessment identified weighing and granulation as high-risk stages, requiring stricter controls. Conclusions: Reducing occupational health risks in the NBL and Penicillin units urgently requires improved engineering controls, PPE protocols and worker training. Model limitations highlight the need for enhanced risk assessment tools to improve safety outcomes.